Comparative "nocebo effects" in older patients enrolled in cancer therapeutic trials: Observations from a 446‐patient cohort. Issue 21 (12th July 2017) - Foster, Jared C.; Le‐Rademacher, Jennifer G.; Feliciano, Josephine L.; Gajra, Ajeet; Seisler, Drew K.; DeMatteo, Ronald; Lafky, Jacqueline M.; Hurria, Arti; Muss, Hyman B.; Cohen, Harvey J.; Jatoi, Aminah
Abstract : BACKGROUND: A nocebo is an inert substance associated with adverse events. Although previous studies have examined the positive (placebo) effects of such inert substances, few have examined negative (nocebo) adverse event profiles, particularly in older patients who have higher morbidity and can experience frequent and severe adverse events from cancer therapy. METHODS: This study focused on placebo/nocebo‐exposed patients who participated in 2 double‐blind, placebo‐controlled, cancer therapeutic studies, namely, North Central Cancer Therapy Group trial NCCTG 97‐24‐51 and American College of Surgeons Oncology Group trial Z9001, with the goal of reporting the comparative, age‐based adverse event rates, as reported during the conduct of these trials. RESULTS: Among the 446 patients who received only placebo/nocebo and who were the focus of the current report, 161 were aged ≥65 years at the time of respective trial entry, and 5234 adverse events occurred. Unadjusted adverse event rates did not differ significantly between patients aged ≥65 years and younger patients (rate ratio, 1.01; 99% confidence interval, 0.47‐2.02), and the findings were similar findings for grade 2 or worse adverse events and for all symptom‐driven adverse events (for example, pain, loss of appetite, anxiety). Adjustment for sex, ethnicity, baseline performance score, and individual trial resulted in no significant age‐based differences in adverse event rates. Similar findings were observed with an age threshold of 70 years. CONCLUSIONS: Adverse events are equally common in older and younger cancer patients who are exposed to nocebo and thus require the same degree of clinical consideration regardless of age. Cancer 2017;123:4193–4198. © 2017 American Cancer Society . Abstract : Nocebo effects are examined in older patients with cancer. On the basis of analyses of 2 large, prospectively conducted studies, adverse events are equally common in older and younger nocebo‐exposed patients with cancer and thus require the same degree of clinical consideration regardless of patient age.